Trends in overweight and obesity among children and adolescents aged 5 to 19 years living in rural areas of low- and middle-income countries: a systematic review: 10.55131/jphd/2025/230224 - Sakai, Moeno; Maeda, Takayo; Shrestha, Gita; Acharya, Shiva; Nurfita Chasanah, Alfi; Nakazawa, Minato (Journal of Public Health and Development, 2025)
The issue of overnutrition in rural areas has often been overshadowed by the focus on urbanization and modernization as the main drivers. Therefore, with this systematic review we aimed to determine trends in overweight and obesity among children and adolescents living in rural areas of low- and middle-income countries (LMICs). We conducted a comprehensive search of MEDLINE and Web of Science, from inception to 06 August 2023. Cross-sectional observational studies reporting on overweight and obesity in children and adolescents living in rural areas of LMICs were independently reviewed by several researchers. Simple linear regression was used to analyze trends in overweight and obesity over time. This study is registered on PROSPERO (CRD42023444823). In total, 176 studies from 132 publications, involving 697,395 participants were analyzed. The prevalence of overweight and obesity increased significantly between 1985 and 2022 (P=0.04 for overweight, P=0.09 for obesity). Subgroup analysis showed a significant increase in the prevalence of overweight and obesity in the East Asia and Pacific region, as well as in middle-income countries, from 1985 to 2021 (P<0.01). The findings of our study highlight the escalating rates of overweight and obesity among children and adolescents in rural areas of LMICs, particularly in East Asia and the Pacific and middle-income countries. Our study emphasizes the urgent need to address this public health challenge to reduce the risks associated with childhood overweight and obesity in rural areas.